Synergistic Stimulation with Different TLR7 Ligands Modulates Gene Expression Patterns in the Human Plasmacytoid Dendritic Cell Line CAL-1 - Tobias Hilbert; Folkert Steinhagen; Christina Weisheit; Georg Baumgarten; Andreas Hoeft; Sven Klaschik (Mediators of Inflammation)
Objective. TLR7 ligation in plasmacytoid dendritic cells is promising for the treatment of cancer, allergy, and infectious diseases; however, high doses of ligands are required. We hypothesized that the combination of structurally different TLR7 ligands exponentiates the resulting immune response. Methods. CAL-1 (human pDC line) cells were incubated with the TLR7-specific adenine analog CL264 and single-stranded 9.2s RNA. Protein secretion was measured by ELISA. Microarray technique was used to detect modified gene expression patterns upon synergistic stimulation, revealing underlying functional groups and networks. Cell surface binding properties were studied using FACS analysis. Results. CL264 in combination with 9.2s RNA significantly enhanced cytokine and interferon secretion to supra-additive levels. This effect was due to a stronger stimulation of already regulated genes (by monostimulation) as well as to recruitment of thus far unregulated genes. Top scoring canonical pathways referred to immune-related processes. Network analysis revealed IL-1β, IL-6, TNF, and IFN-β as major regulatory nodes, while several minor regulatory nodes were also identified. Binding of CL264 to the cell surface was enhanced by 9.2s RNA. Conclusion. Structurally different TLR7 ligands act synergistically on gene expression patterns and on the resulting inflammatory response. These data could impact future strategies optimizing TLR7-targeted drug design.